2016
DOI: 10.18865/ed.26.2.213
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Creatinine-based Kidney Function Estimates Among HIV-infected Adults

Abstract: <p><strong>Objective</strong>: The aim of our study was to investigate whether current eGFR equations in clinical use might systematically overestimate the kidney function, and thus misclassify CKD status, of Black Americans with HIV. Specifically, we evaluated the impact of removing the race coefficient from the MDRD and CKD-EPI equations on comparisons between Black and White HIV-infected veterans related to: 1) the prevalence of reduced eGFR; 2) the distribution of eGFR values; and 3) the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…21 Previous data from Africa (and African European) also suggested that such an ethnic factor was not valuable. [18][19][20][21][22]29,30 Regarding ethnicity, we showed that FAS SCr af had the same global performance as FAS SCr observed in Whites, both in patients with low GFR values and in subjects with high GFR values. This is easily explained, as Q af was not different from the Q values observed in Whites.…”
Section: Discussionsupporting
confidence: 51%
“…21 Previous data from Africa (and African European) also suggested that such an ethnic factor was not valuable. [18][19][20][21][22]29,30 Regarding ethnicity, we showed that FAS SCr af had the same global performance as FAS SCr observed in Whites, both in patients with low GFR values and in subjects with high GFR values. This is easily explained, as Q af was not different from the Q values observed in Whites.…”
Section: Discussionsupporting
confidence: 51%
“…Glomerular filtration rate (GFR) was estimated using the 4-variable MDRD (Modification of Diet in Renal Disease) Study 20 and CKD-EPI (CKD Epidemiology Collaboration) 21 equations. The MDRD Study and CKD-EPI equations without the race factor were used for estimating GFR in this study given that recent studies [22][23][24] have suggested that the inclusion of race may generate less precise estimates in the black population. For computations requiring estimated GFR, values from the CKD-EPI equation were used.…”
Section: Ethical Approvalmentioning
confidence: 99%
“…Previous studies have identified differences between renal function estimates among Black patients. 12,[16][17][18][19][20][21] Booysen et al 20 and Omuse et al 17 reported that CKD-EPI was the most accurate estimate in Black South Africans and Kenyans, respectively. However, Eastwood et al 18 determined that CKD-EPI without race was more accurate in lean Black patients in Ghana.…”
Section: Discussionmentioning
confidence: 99%
“…We included patients with or without CKD, and in a subgroup analysis by CKD stage, we found the highest rate of discordance in patients with CKD stage 4. Anker et al 19 performed a large cohort study in the Department of Veteran Affairs HIV Clinics, which included 12 029 Black patients. They reported that whereas the mean measured GFR in Black patients was only 6.6% higher when compared with White patients, the eGFR calculated by the CKD-EPI equation was 16% higher in Black patients than in White patients.…”
Section: Discussionmentioning
confidence: 99%